2010
DOI: 10.1016/j.jim.2010.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantification of Panton–Valentine leukocidin in Staphylococcus aureus cultures by ELISA and Western blotting: Diethylpyrocarbonate inhibits binding of protein A to IgG

Abstract: Enzyme-linked immunosorbent assay (ELISA) and Western blotting are common techniques used to detect and quantify proteins in Staphylococcus aureus culture supernatants, such as PantonValentine leukocidin (PVL). However, protein A (Spa) secreted by most S. aureus strains may interfere with these assays by binding to the capturing and detecting antibodies. Here, we have shown that the addition of diethylpyrocarbonate (DEPC) inhibits the binding of Spa to rabbit anti-PVL used as the capturing antibody in ELISA. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Equal amount of protein from each isolate was resolved on 12% acrylamide gels and transferred to nitrocellulose membrane using semidry transfer technique. Membrane was blocked using 5% skim milk powder and 5 mM DEPC in PBS pH 6.0 for 20 minutes at room temperature, washed thrice with PBS pH 7.4 containing 0.1% tween 20 (PBST), followed by overnight incubation at 4°C with 1∶10,000 dilution of rabbit anti SEA antibody (Sigma Aldrich, India) in PBS containing 0.05% tween 20 [45]. Membranes were washed thrice with PBST followed by incubation with 1∶20,000 dilution of Anti rabbit IgG-HRP conjugate (Sigma Aldrich) in PBS containing 0.05% tween 20.…”
Section: Methodsmentioning
confidence: 99%
“…Equal amount of protein from each isolate was resolved on 12% acrylamide gels and transferred to nitrocellulose membrane using semidry transfer technique. Membrane was blocked using 5% skim milk powder and 5 mM DEPC in PBS pH 6.0 for 20 minutes at room temperature, washed thrice with PBS pH 7.4 containing 0.1% tween 20 (PBST), followed by overnight incubation at 4°C with 1∶10,000 dilution of rabbit anti SEA antibody (Sigma Aldrich, India) in PBS containing 0.05% tween 20 [45]. Membranes were washed thrice with PBST followed by incubation with 1∶20,000 dilution of Anti rabbit IgG-HRP conjugate (Sigma Aldrich) in PBS containing 0.05% tween 20.…”
Section: Methodsmentioning
confidence: 99%
“…However, this method requires antibodies from two animal sources. Several other methods were reported to reduce SpA interference in single antibody ELISAs by employing several modifications, such as incubation in diethylpyrocarbonate (DEPC; Nguyen et al 2010), biotinylation of rabbit IgG to mask the protein A binding site (Hahn et al 1986), or removal of protein A from the sample by immobilized IgG (Hjelm et al 1972). However, we have observed that most of these methods are not reliable, given the reduction in sensitivity by DEPC treatment and persistent cross-reaction of protein A with biotin-labeled IgG.…”
Section: Discussionmentioning
confidence: 99%
“…One important point to be considered is that Staphylococcus aureus produces protein A (6), which reacts with the Fc region of IgG, potentially causing false-positive results in immunoassay systems (18,20). We used the monoclonal antibodies to IgG1 and IgM for the present ICT.…”
Section: Discussionmentioning
confidence: 99%
“…The VOL. 18,2011 SIMPLE DETECTION OF PBP2Ј 249 chromatograph was developed for 10 min, and the reaction products at the test line and the control line were observed macroscopically. The cross-reactivity test was carried out using the strains used for indirect ELISA, except for the MRSA strains.…”
Section: Expression and Purification Of His-tagged Recombinant Pbp2 (mentioning
confidence: 99%